Elderly and fire safety: using serious games to elicit human behaviour in evacuation scenarios. (2016) - Almeida, João E.; Rossetti, Rosaldo J.F.; Faria, Brígida Mónica; Coelho, António Leça
The problem of leaving a building while facing some emergency has gained much attention from the scientific community. Evacuation simulators can help emergency planners to assess the safety of buildings. However, such simulators still lack behavioural knowledge to increase their accuracy. The elderly have specific behaviour idiosyncrasies. This paper presents a set of experiments designed to elicit human behaviour in evacuation scenarios using serious games, applied to a population sample of 20 adults aged over 65 years. They were presented three experiments (alarm id, exit-choice in five different situations and auditorium with four situations) and their reactions were collected. Results were analysed and compared with previous similar experiments. Future directions in this research include: to expand and to refine data collection to other scenarios and perform massive data collection using the internet; and to use this data to feed and enhance existing crowd simulators particularly for evacuation purposes.